2019
DOI: 10.1590/1807-1929/agriambi.v23n7p499-505
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of probability in obtaining intensity-duration-frequency relationships of rainfall occurrence for Pelotas, RS, Brazil

Abstract: Based on historical series, for each locality, equations can characterize the relationship between intensity, duration and frequency of rainfall occurrence. The objective of this study was to present two equations that can describe the occurrence of intense rainfall in Pelotas, RS state, over the period 1982-2015. The two equations were denominated conventional and hybrid, depending on the probabilistic model used. Following the conventional methodology, the parameters of Normal, Log-Normal, Gumbel and Gamma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…The results for each duration and return period analyzed showed that the maximum rainfall adjusted for the summer using the Gumbel distribution was similar to that obtained through the IDF, as estimated by Dorneles et al (2019).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The results for each duration and return period analyzed showed that the maximum rainfall adjusted for the summer using the Gumbel distribution was similar to that obtained through the IDF, as estimated by Dorneles et al (2019).…”
Section: Resultssupporting
confidence: 73%
“…The results of the performance indices showed that the maximum summer rainfall series was similar to that obtained using the conventional method of Dorneles et al (2019). The RMSE values were 7.34 < x < 10.41, with the lowest RMSE value obtained for a 100-year return time.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations